Tambora : the Eruption That Changed the World. - Wood, Gillen DArcy (Princeton University Press, 2014)
When Indonesia's Mount Tambora erupted in 1815, it unleashed the most destructive wave of extreme weather the world has witnessed in thousands of years. The volcano's massive sulfate dust cloud enveloped the Earth, cooling temperatures and disrupting major weather systems for more than three years. Communities worldwide endured famine, disease, and civil unrest on a catastrophic scale. Here, Gillen D'Arcy Wood traces Tambora's global and historical reach: how the volcano's three-year climate change regime initiated the first worldwide cholera pandemic, expanded opium markets in China, and plunged the United States into its first economic depression. Bringing the history of this planetary emergency to life, Tambora sheds light on the fragile interdependence of climate and human societies to offer a cautionary tale about the potential tragic impacts of drastic climate change in our own century.